Immunomodulation of the Ocular Surface in Severe Dry Eye Disease: Expert-Driven Literature Review on Treatment Strategies with Description of Representative Challenging Cases - Тройченко, Людмила Федорівна (My University, 2026)
Introduction Dry eye disease (DED) is a multifactorial inflammatory disorder characterized by tear-film hyperosmolarity, immune activation, and neurosensory dysfunction, which contribute to sustained ocular surface damage. Severe DED is common in autoimmune diseases, especially Sjögren syndrome (SS) and rheumatoid arthritis (RA), and is often refractory to first-line treatments. Methods Current evidence on anti-inflammatory therapies was summarized by experts, and the management of challenging cases of autoimmune-related DED followed in different tertiary centers was presented. Results Short courses of topical corticosteroids rapidly suppress disease flares and improve clinical signs, including breakup time and ocular surface staining. However, careful stewardship is required, as prolonged use may elevate intraocular pressure, induce cataract formation, and increase infectious risk. For long-term control, immunomodulators such as cyclosporine A (CsA), lifitegrast, and tacrolimus attenuate T-cell–mediated inflammation, promote goblet cell recovery, and stabilize the tear film. Newer CsA formulations have further improved bioavailability and tolerability. Five challenging cases including DED associated with SS or RA, refractory keratopathy, and corneal epithelial defect were described. Management included biological tears, lid-based care, and punctal plugs combined with once-daily CsA, leading to re-epithelialization, symptom relief, and visual stabilization. Adjunctive measures included oral doxycycline to improve meibomian gland function and reduce inflammation. Regular follow-up optimized treatment tapering, safety monitoring, and patient adherence. In two cases, urgent surgical intervention (conjunctival flap, amniotic membrane transplantation, and penetrating keratoplasty) was required. Conclusions Autoimmune-related DED requires a stepwise treatment regimen for the stabilization of the ocular surface and the prevention of irreversible damage. This approach involves an initial short course of corticosteroids, followed by sustained immunomodulation (with CsA as the cornerstone), and supplemented by adjunctive therapies targeting meibomian glands and ocular surface epithelium. Multidisciplinary coordination and regular monitoring are essential for maintaining long-term ocular surface homeostasis and satisfactory quality of life and visual function.